Surgical Treatment in Serious Traumatism of Thoracic Wall. - Ruiz Liard, Alfredo; Croci, Fabio; Gastambide, Carmelo (Cirugía del Uruguay, 1984)
Since 1977 to date, authors have carried out the surgical stabilization of serious parietal thoracic wall traumatisms, volets and depletions, at the Medica! Services Central Department. Eighteen patients have been operated, with a mortality rate of 5.5% and highly stimulating results in terms of functional and anatomic recovery